PERBANDINGAN DEEP NECK FLEXOR STRENGTHENING EXERCISE DENGAN MCKENZIE NECK EXERCISE UNTUK KOREKSI POSTUR LEHER PADA SISWA PENDERITA FORWARD HEAD POSTURE DI SMA N 1 SEMARAPURA - Gede Eka Juli Prasana; I Nyoman Adiputra; I Made Krisna Dinata (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
This study aims to compare deep neck flexor strengthening exercise intervention with mckenzie neck exercise to correct the neck posture of student with forward head posture. Using experimental design with Pre-Test and Post-Test Group Design involves a sample of 24 people divided into 2 groups. Group I was given deep neck flexor strengthening exercise intervention and Group II was given mckenzie neck exercise intervention. Hypothesis Test using paired sample t-test obtained result p = 0.592 with average difference in Group I 7.58 ± 4.39 whereas Group II got difference mean 8.5 ± 3.84. These results showed no significant difference in craniovertebral angle elevation before and after intervention in both groups. Keywords : forward head posture, craniovertebrae angle, deep neck flexor strengthening exercise, mckenzie neckexercise,